Daredevil ebook Guardian devil. - Smith, Kevin (Daredevil (1998)., 2012)
Collects Daredevil (1998) #1-8. A scared teenager on the run. An infant child some say is humanity's savior. A former lover whose life is now hobbled by a terrible secret. A law partner accused of a horrible crime. A city being overcome by an inscrutable menace. They need a guardian. Someone to protect them. Someone with faith in them. They need Daredevil.